The New WHO Classification of Brain Tumours - Paul Kleihues; Peter C. Burger; B. W. Scheithauer (1993)
The new edition of the World Health Organization (WHO) book on ‘Histological Typing of Tumours of the Central Nervous System’ reflects the progress in brain tumour classification which has been achieved since publication of the first edition in 1979. Several new tumour entities have been added, including the pleomorphic xanthoastrocytoma, central neurocytoma, the infantile desmoplastic astrocytoma/ganglioglioma, and the dysembryoplastic neuroepithelial tumour. The list of histological variants has also been expanded. In line with recent morphological and molecular data on glioma progression, the glioblastoma is now grouped together with astrocytic tumours. The classification of childhood tumours has been largely retained, the diagnosis primitive neuroectodermal tumour (PNET) only being recommended as a generic term for cerebellar meduiloblastomas and neoplasms that are histologically indistinguishable from medulloblastoma but located in the CNS at sites other than the cerebellum. The WHO grading scheme was revised and adapted to new entities but its use, as before, remains optional.